Clozapine treatment of a Japanese patient during pregnancy: Effect on fetal heart rate - Shunya Aoki; Katsutoshi Takada; Tatsuru Sugama; Mitsugi Kimiwada; Tatsuya Hoshino; Takaoki Kaneko; Shintaro Obata; Yasuhiro Ota; Satoshi Toishi; Kaori Koike; Hirokazu Akada; Takahisa Saiga; et al. (Neuropsychopharmacology Reports)
Abstract The current literature on the effects of clozapine on pregnancy is limited, and no cases of pregnant Japanese women have been reported. Decreased variability in the fetal heart rate due to clozapine exposure has been reported in countries other than Japan, but its association with serum concentrations of clozapine has not been documented. In this case, a 29‐year‐old Japanese primipara with treatment‐resistant schizophrenia taking clozapine 250 mg/day experienced pregnancy. The pregnancy progressed without complications. At 40 weeks and 2 days of gestation, the patient developed premature rupture of membranes, and decreased variability in the fetal heart rate and variable deceleration were observed, leading to an emergency cesarean section. The neonate had no congenital malformations, metabolic disorders, seizures, floppy infant syndrome, leukopenia, or neutropenia. Serum concentrations of clozapine and norclozapine (N‐desmethylclozapine), measured in the mother and in the neonate immediately after birth, suggested that clozapine and norclozapine were transported to the fetus during pregnancy. Based on these observations, the present case suggests that high fetal serum concentrations of clozapine and norclozapine may affect fetal heart rate. This case report concludes that, with careful monitoring, Japanese women taking clozapine can deliver successfully and emphasizes the importance of monitoring serum clozapine concentrations and fetal cardiac function throughout pregnancy, with particular attention to the later stages.